VOCABULARY ENRICHMENT THROUGH QIRA’AH AL-RASHIIDAH: A CONTEXTUAL APPROACH IN AN ARABIC LANGUAGE IMMERSION ENVIRONMENT: PEMBERDAYAAN KOSA KATA MELALUI QIRA’AH AL-RASHIIDAH: PENDEKATAN KONTEKSTUAL DALAM LINGKUNGAN IMERSI BAHASA ARAB - Segaf Baharun; Arisandi, Yusuf (Prodi Pendidikan Bahasa Arab Fakultas Agama Islam, 2025)
This study investigates the use of Qira’ah al-Rashiidah as a contextual tool for vocabulary enrichment in an Arabic language immersion environment at Pesantren Darullughah Wadda’wah. Despite being widely used, Qira’ah al-Rashiidah is often underestimated due to its outdated appearance and lack of visual clarity. Using a qualitative approach, this research involved 30 first-year Tsanawiyah students over a two-month period. Data were collected through observations, interviews, and document analysis. The findings reveal that contextual vocabulary strategies, such as identifying thematic words, using visual mind maps, and conducting discussions significantly improved students' lexical retention and engagement. Students showed better comprehension and used new vocabulary more confidently in speaking and writing. The study highlights the value of integrating classical texts with modern pedagogical methods to revitalize Arabic vocabulary learning in pesantren-based education. Key words: Arabic Immersion, Contextual Approach Qira’ah Al-Rashiidah, Vocabulary Enrichment.